On the relation between organizational culture and leadership: An empirical analysis - Antoniοs D. Kargas; Dimitrios Varoutas; Tahir Nisar (Cogent Business & Management, 2015)
Leadership and organizational culture are considered to be two of the most crucial organizational elements in order for firms to compete successfully and to gain sustainable advantage. We examine the interconnection between the aforementioned elements and create an empirical link based on data drawn from a competitive industry. The results indicate a strong relationship between these two operational factors, while factors' coordination (identical cultural type and leadership style) enforces this relationship. Moreover, it is investigated whether market conditions, such as strength of competition and “operational age and size,” can determine the extent and the direction of the relationship. Market competition seems to affect the direction of the relationship, while operational age and size affect the relevant extent.
Keywords: 650